Utilization Of Secondary Metabolite Compounds from 96% Ethanol Extract of Pidada Leaves (Sonneratia caseolaris L) as an Antibacterial against Bacillus subtilis and Pseudomonas aeruginosa Bacteria - Putriani, Kony; Serawaidi, Nadya Putri Aulya; Roswatidi, Eva; Andini, Febria (Poltekkes Kemenkes Riau, 2024)
Infectious diseases are still a serious problem, and it is important to increase other sources of antimicrobial drugs from natural ingredients, one of which is the pidada plant. This research aims to determine the content of secondary metabolite compounds found in pidada leaves and determine the inhibitory power of pidada leaf extract against the bacteria Bacillus subtilis and Pseudomonas aeruginosa. This type of research is a real experimental laboratory with a maceration extraction method using 96% ethanol solvent and antibacterial testing using the well diffusion method with variations in extract concentration of 80%, 60%, 40% and 20%. The research results show that the extract contains flavonoids, phenolic compounds, saponins, tannins and steroids. The results of the antibacterial activity test showed that there was an inhibitory power at a concentration of 80%, namely Bacillus subtilis bacteria of 19.13 mm in the intermediate category and Pseudomonas aeruginosa bacteria of 17.18 mm in the intermediate category. The results showed that the ethanol extract of pidada leaves can inhibit the growth of Bacillus subtilis and Pseudomonas aeruginosa bacteria.